THE PROBLEM OF ASSESSING THE EXPECTED CONSEQUENCES OF ECONOMIC POLICY (Globalization and Business, 2023)
The starting point for economic policy analysis is the difference between what exists and what should exist. Therefore, opinions (views) about what should be, can be used to assess the observed economic situation and development. It is possible to come up with recommendations on how to avoid the differences between what exists and what should exist. In reality, we find factual events that any person can check. There are also desirable events that go beyond such a check. It is on the basis of their comparison that the content of both evaluations and recommendations is formed. Normative views express subjective desires, so the result of the evaluation can not be considered "right" or "wrong". It is possible that the entity (or economic interest group) will consider them acceptable or even reject them.As a result of the significant increase in economic uncertainty in modern conditions, the complex presentation of the targeted aspect of economic policy, as well as the substantial improvement of the degree of policy adaptability itself, taking into account the requirements for ensuring the continuity of systemic long-term forecast work, are especially relevant.